Living on Shaky Ground: The science and story behind New Zealand’s earthquakes - Campbell, Hamish (New Zealand Science Review, 2015)
​This is much more than just another very handsome and beautifully illustrated book. It is well-researched, thorough, substantive, accurate, carefully crafted, well-organised and superbly presented. It is the perfect book-owner’s almanac featuring all the major historic earthquakes that New Zealand has experienced within living memory....and obviously prior to 2014. I must admit that I approached the book with some trepidation, some jaundice even, simply because there are a number of books available on the market that address New Zealand’s earthquake record and/or the geological explanation for them. However, this book is significantly more comprehensive and is laced with many well-chosen photographs that I have not seen before. Furthermore, they are well-proportioned, not too small, and all have adequate and easy to read captions. Photographs are so important, especially to people like me who grew up on a diet of Tintin. They make or break your mind when it comes to making that purchasing decision. This book is right over there on the ‘yes, must have’ side.